PENGETAHUAN ORANGTUA TENTANG PENTINGNYA KELENGKAPAN IMUNISASI - Alfionita, Dina; S, Cucuk Kunang; S, Rina Puspita (Nusantara Hasana Journal, 2022)
Immunization is a key component of primary health care and is a human right. Immunization is the best form of health investment and is a technique for preventing and controlling infectious disease outbreaks (World Health Organization (WHO), 2020).The purpose of the study was to determine the relationship between parental knowledge about the importance of immunization and completeness of immunization. The design of this study used descriptive analytic with a cross sectional approach. This type of research uses a sampling technique in this study using accidental sampling, the research sample of the community who attended was 133 respondents with the sample criteria of age, gender, and education. The results of this study obtained a good level of knowledge and good immunization completeness as many as 68 respondents (51.1%) chi-square statistical test obtained p-value of 0.000 or <0.05. The conclusion of the research there is a significant relationship between parental knowledge about the importance of immunization against complete immunization in the community of Sukalangu Village, Pandeglang Regency, Banten Province. It is hoped that it can be used as a reference by parents so that parents have sufficient knowledge about the importance of immunization so that children can be immunized completely and children become healthy.